Fast Fulfillment : The Machine That Changed Retailing. - Das, Sanchoy (New York : Business Expert Press, 2021)
Managers are frustrated just reading about how great Amazon is, and how startups are innovating fantastic technology driven processes. Here is the book, written in a simple easy to read style which unravels the technical mystery of the fulfillment machine. It levels the knowledge field, reveals the secrets of fast fulfillment, and helps the reader construct a plan to innovate and be ready to face the disruptors. This book provides insights and process details of how to design and build disruptive innovations, so that you are not flying blind or just throwing darts in an effort to pivot/expand to the online order fulfillment world.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Foreword -- Acknowledgments -- Chapter 1: Paradigm Shift in Retailing Logistics-Fulfillment -- Chapter 2: The Evolution of Online Retail -- Chapter 3: Speed-The Necessary Condition -- Chapter 4: Mathematics of Fast Fulfillment -- Chapter 5: Innovative Differentiators -- Chapter 6: Last Mile Fulfillment -- Chapter 7: Humans and Automation -- Chapter 8: Brownian Organization -- Chapter 9: Modeling and Optimization -- Chapter 10: Machine Building -- Chapter 11: Team Innovation -- Appendix: Innovation Toolbox -- Bibliography -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Business logistics; Materials management; Amazon.com (Firm).; Electronic books